2020
DOI: 10.1038/s41598-020-66245-w
|View full text |Cite
|
Sign up to set email alerts
|

Mudstone creep experiment and nonlinear damage model study under cyclic disturbance load

Abstract: to study the creep characteristics of mudstone under disturbed load, creep rock triaxial compression disturbance tests under different disturbance amplitudes and frequencies are conducted using a self-made triaxial disturbed creep test bench for rock. The influence of different factors on the creep deformation law of each stage is analyzed. The results show that the disturbance effect has a significant impact on the creep properties of mudstone, and various factors have different effects on the creep stages. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Scholars have achieved fruitful advancements in studying rock creep models, which are mainly categorized into empirical and component combination models 4 – 6 . Empirical models are based on experimental phenomena and laws 7 10 ; component combination models are based on essential components, such as elasticity, viscosity, and plasticity, and are formed by series and parallel methods 11 , 12 . Wang et al 13 established a six-element composite creep model by analyzing the loading and unloading creep curves of limestone.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have achieved fruitful advancements in studying rock creep models, which are mainly categorized into empirical and component combination models 4 – 6 . Empirical models are based on experimental phenomena and laws 7 10 ; component combination models are based on essential components, such as elasticity, viscosity, and plasticity, and are formed by series and parallel methods 11 , 12 . Wang et al 13 established a six-element composite creep model by analyzing the loading and unloading creep curves of limestone.…”
Section: Introductionmentioning
confidence: 99%
“…Then, applying Burger's model into DEM, Li et al [14] studied the rheological behavior of soft rock; Guo et al [15] studied the time-dependent mechanics of sandstone. However, many creep tests of soft rock [14,[16][17][18][19][20] have shown that the full creep includes attenuated, steady, and accelerated creep. The classic Burger's model can only reveal the first two creep stages [21], which is weak in describing the damage process.…”
Section: Introductionmentioning
confidence: 99%
“…rough qualitative analysis, the types of creep disturbance failure were classified into two types. Wang et al [24,25] carried out creep disturbance experiments with different perturbation amplitudes and frequencies on different soft rock specimens (gneiss and mudstone) using a stepwise loading method, and according to the disturbance creep characteristics, a creep perturbation damage model was established.…”
Section: Introductionmentioning
confidence: 99%